The expression is:
[tex]speed(minutes)=3\frac{km}{h} ^{minutes} \\\\speed(15minutes)=(3^{15})\frac{km}{4} =14348907\frac{km}{g}[/tex]
Why?
From the statement we know that the spaceship travels 3 times faster each minute that it traveled during the minute before, it can be expressed using an exponential function, its base will be the starting speed (during the first minute).
The expression will be:
[tex]speed(minutes)=(3^{minutes})\frac{km}{h} \\\\speed(15minutes)=(3^{15})\frac{km}{h}=14348907\frac{km}{h}[/tex]
Have a nice day!